Early marriage, social networks and the transmission of norms - Niaz Asadullah; Zaki Wahhaj (University of Kent, School of Economics, 2016)
We investigate whether female early marriage is a conduit for the transmission of social norms, specifically norms relating to gender roles and rights within the household. We exploit differences in the age of onset of menarche between sisters as an exogenous source of variation in marriage age. This approach allows us to control for beliefs and attitudes that are transmitted from parents to children. We find that early marriage increases agreement with statements supportive of gender bias in the allocation of resources and traditional gender roles. The woman's own schooling, her husband's schooling, and her social network together account for, at most, one-third of the estimated effect, suggesting that the major pathway for norm transmission is the experience of early marriage itself.
Keywords: J12; J16; Z10; 330; Gender Roles; Social Norms; Schooling; Household Decision-Making